Son of machinery guard, Cho Bo Wen receives Malakoff Excellence Award - Siti Nurfarmy, Ibrahim (2022)
PAYA BESAR, 6 November 2022 – The recipient of the Malakoff Corporation Bhd. Excellence Award, Cho Bo Wen aspires to become a successful engineer in the future.